Epilepsy and quality of life in Iranian epileptic patients - Bahareh Honari; Seyed Mehran Homam; Maryam Nabipour; Zahra Mostafavian; Arezou Farajpour; Nyusha Sahbaie (SpringerOpen, 2021)
Abstract Background Epilepsy is one of the most common neurological disorders with physical, emotional, and social consequences. Previous studies indicate that epilepsy symptoms can highly affect the epileptic patients' satisfaction in life. The aim of the present study is to investigate the QOL of People with Epilepsy (PWE) in Khorasan Razavi province, Iran. Methods In this study, 100 patients were randomly selected. After confirmation of the diagnosis of epilepsy by neurologists and fulfilling the entrance criteria, patients completed the Quality of Life in Epilepsy-31 inventory (QOLIE-31) questionnaire. Finally, data was analyzed statistically by SPSS software. Results The study sample comprised 100 PWE, aged 18-74 years (34 ± 13), of whom 58 (58%) were females. Tonic-colonic seizure was the most common (60%) type of seizure. The obtained score of each subscale and the range of the QOLIE-31 total score was 16.40-79.18 with the mean of 50 (SD = 16). The energy-fatigue subscale score was significantly higher in patients younger than 35 (p = 0.018). The data analysis showed that the seizure worry subscale was significantly higher in single patients (p = 0.04). Duration of epilepsy had a positive correlation with QOLIE-31 total score (p = 0.038), and a negative relationship with energy-fatigue subscale (p = 0.018). In contrast with previous studies, which reported the frequency of the epileptic episodes as the most important predictor of QOL, our results showed no significant correlation between the number of the episodes and overall QOL score (p = 0.063). However, the number of episodes was significantly correlated with emotional well-being and cognition subscales. Furthermore, the results indicated that poor QOL score is correlated with depressed mood. Conclusion In fact, the ultimate and preferred outcome of all treatments and care interventions is the patient's QOL. Thus, improvement of the QOL by means of obtaining more information about its contributing factors, in PWE should be one of the main goals in the patients' treatment.